Productivity of wheat varieties under poplar (Populus deltoides Bartr. ex Marsh.) based agroforestry system in Northern India - SIROHI, CHHAVI; Kumar, Parvinder; Dhillon, R.S.; Bhardwaj, K.K.; Handa, A.K.; Arunachalam, A.; Kumari, Sushil; Ahlawat, K.S. (Indian Journal of Agroforestry, 2023)
The current study was carried out to examine the performance of three wheat varieties under varying spacing geometry (3×3, 4×3, 5×3, 6×3, 7×3 and 8×3 m) of an already existing three-year-old poplar plantation during 2019-20. In 3×3 m spacing, poplar growth was observed to be substantially higher. Under various spacing geometries of poplar plantation, the growth and yield-attributing characteristics of the wheat varieties (WH-1105, HD-2967 and WH-711) were drastically reduced when compared to sole crop (devoid of trees). Wheat variety HD-2967 exhibited the highest grain yield (4.68 t/ha) followed by WH-711 (4.25 t/ha) in wider spacing (8×3 m) of poplar based agroforestry system (AFS). The grain yield of wheat declined significantly with the decrease in spacing. On an average, the highest per cent reduction in grain and straw yield over control was recorded in WH-1105 (27.2 and 15.3%) followed by WH-711 (19.7 and 13.8%) and HD-2967 (14.7 and 12.1%) under 3×3 m spacing. In the present study, the rate of decrease in straw yield was comparatively lower than grain yield under different spacings of poplar. The overall reduction in grain and straw yield was more under closer spacing (3×3 m) may be due to more vigor growth of poplar tree and obviously more completion for moisture, nutrients and solar radiation between the annual crops and poplar plants